2013
DOI: 10.7243/2052-6962-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Advances in cystoscopic surveillance of superficial bladder cancer: detection of the invisible tumor

Abstract: Objectives: To review recent advances in imaging modalities available for diagnosis and surveillance of superficial bladder cancer. Methods: Detailed PubMed searches were performed using the terms "fluorescence cystoscopy," "narrow-band imaging," and "optical coherence tomography" with "bladder cancer" and "urothelial carcinoma." Relevant literature was selected for analysis. We explored the clinical evidence to support the use of these technologies for the detection and surveillance of bladder cancer. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The FNS parameters of the structure were determined for all the images obtained in such windows (typically, there were 5-8 images) [26]. It has previously been demonstrated [6] that, out of the entered 3D parameters of the structure in the specified range of spatial dimensions, the following ones are most sensitive to pathological changes in the tissue: parameter σ, which is a measure of the jump-like irregularities of the chaotic surface profiles against the low frequency -baselineit is determined as a "stepwiseness factor" of the chaotic component of the profile; and parameter S(L 0 -1 ), which is a measure of the spike-like irregularities of the profile being observed -it is determined as the "spikiness factor" of the surface structure. These two parameters were considered as the fundamental ones for the FNS parametrization of the bladder tissue AFM images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FNS parameters of the structure were determined for all the images obtained in such windows (typically, there were 5-8 images) [26]. It has previously been demonstrated [6] that, out of the entered 3D parameters of the structure in the specified range of spatial dimensions, the following ones are most sensitive to pathological changes in the tissue: parameter σ, which is a measure of the jump-like irregularities of the chaotic surface profiles against the low frequency -baselineit is determined as a "stepwiseness factor" of the chaotic component of the profile; and parameter S(L 0 -1 ), which is a measure of the spike-like irregularities of the profile being observed -it is determined as the "spikiness factor" of the surface structure. These two parameters were considered as the fundamental ones for the FNS parametrization of the bladder tissue AFM images.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative processing of 3D OCT images was demonstrated to significantly increase the diagnostic performance of the method for in situ detection of bladder carcinomas [3][4][5]. Meanwhile, an analysis of a large number of works on the use of OCT for bladder cancer visualization by Hale and Deem [6] indicated that cases of false positive cancer diagnoses are fairly typical for OCT against a background of severe inflammation as well as in cases of the diagnosis of cancer in the region of the postoperative scar.…”
mentioning
confidence: 99%
“…Abdominal CT has a sensitivity of 80% for upper urinary tract tumor and a sensitivity of 60% for bladder tumors [3,4]. Cystoscopy has a sensitivity of 62-84% in white light cystoscopy [5]. Retrograde pyelography has a sensitivity of 72% when being read by urologist in the operation room [6].…”
Section: Discussionmentioning
confidence: 99%